Flipped Classroom Strategy in Elementary Schools: A Conceptual Review for Strengthening Character and Global Insight - Hana Gardenia Mahbubah; Khosiah; Nurul Fadilah; Bisri Musthofa (Universitas Ahmad Dahlan, 2026)
This study aims to examine the Flipped Classroom strategy in learning Natural Sciences (IPA) in elementary schools, especially in shaping the character and global insight of students. The method used is descriptive qualitative with a library research method, which analyzes various literature sources such as relevant and up-to-date scientific journals. The results show that Flipped Classroom encourages independent learning outside the classroom and collaborative activities in the classroom, which significantly improves students' conceptual understanding as well as basic scientific skills. In addition, this strategy also strengthens character traits such as independence, responsibility and tolerance, while expanding students' global horizons through access to international learning resources. The implications of this research emphasize the importance of education system support, teacher training, and the role of parents to ensure the successful implementation of this strategy in creating a learning process that is holistic, contextual, and relevant to the demands of 21st century education.